THE EFFECT OF FINANCIAL DISTRESS AND TRANSFER PRICING ON TAX AVOIDANCE WITH FIRM SIZE AS A MODERATING VARIABLE - Yuni Isnaini; Ikhsan Budi Riharjo (Universitas Tulungagung, 2026)
This study investigates the effect of financial distress and transfer pricing on tax avoidance, with firm size as a moderating variable. Furthermore, the population consists of Property and Real Estate companies listed on the Indonesia Stock Exchange (IDX) during the 2021-2024. The study applies quantitatively. The data were collected using purposive sampling with 140 data observations. Moreover, the data were taken from financial statements that were published into the official website (www.idx.co.id). The independent variables were financial distress as well as transfer pricing. Meanwhile, the dependent variable was tax avoidance, with firm size as a moderating variable. Additionally, the data were analyzed using multiple linear regression analysis with Moderated Regression Analysis (MRA). As a result, it shows that financial distress has a positive and effect on tax avoidance. However, transfer pricing has a negative effect on tax avoidance. In addition, firm size is not proven to moderate the effect of financial distress and transfer pricing, on tax avoidance.